Protection of Personal Data and its status as a Fundamental Right - In the scope of International Law and EU Law - Hagsberg, Monica (My University, 2019)
Personal data protection has raised discussion during the recent years both in international and national level. With the development of technology, internationalism and the economy it is more and more important to protect the personal data. The adequate way to protect the personal data needs to be considered thoroughly; should it be protected with secondary legislation or with fundamental legislation? During the recent years, the personal data protection legislation in both international and national level has increased. Despite this, the protection of personal data faces threads and challenges every day. These threads and challenges emerge from the inconsistency of international and national data protection legislations, from terrorism and crime, and from the economic and technological development. Also the collisions between different fundamental rights are challenging. For instance, it is not always easy to assess the order of importance between the personal data protection and the right to free flow of data. In this thesis I shall research the status of personal data protection in international level and in international jurisdiction. I will start my research by assessing the threads and challenges personal data protection faces every day. I shall then take a closer look into the relevant European Union law and then to international law. I shall also make a slight comparison between the EU law and the international law. My goal is to figure out the actual challenges and threads to personal data protection and, also, the legal protection that personal data needs and already has. I believe I have reached this goal. I believe that the personal data should be protected as a fundamental right, but it hasn’t reached this status in international level yet. For the data protection to reach this status as a fundamental right, international legislations and regulations needs to be revised. My research methods have mostly been legal dogmatic. My research is mainly based on the relevant legal literature, sources of laws and other written legal sources. The empiric parts in this thesis are mainly from the author herself.